PENGARUH PENGGUNAAN ABU BAWAH SEBAGAI SUBSTITUSI PASIR DALAM PEMBUATAN BATA BETON - Nauval Rabbani (LPPM Universitas Pekalongan, 2021)
Green materials are being developed by researchers and entrepreneurs because they can help manage excess waste by turning the waste into something useful and profitable. one of the uses that can be done in the construction sector is the use of these wastes into structural materials such as concrete bricks for wall filling. One of the wastes that can be used is coal burning waste from textile factories. This research will utilize one of the coal wastes, namely bottom ash as a partial substitution of sand for concrete bricks to see its effectiveness. The research was conducted by making several variations of the mixture using bottom ash with rate of 0%, 15%, 30%, and 45% as a substitute for sand. The test object is made in the size of 24 cm x 12 cm x 6 cm and is treated until the compression test which is 28 days. The results obtained are the compressive strength of concrete brick with bottom ash substitution is lower than concrete brick without bottom ash, but based on SNI 03-0349-1989 the quality of the concrete brick can be classified into grade 1 where it is the highest grade with a minimum compression strength of 100 kg/cm2